Taping techniques for TFCC and ECU injuries on the Sony Ericsson WTA Tour - Stroia, K.; Baudo, M.; Martin, K. (Medicine and Science in Tennis, 2009)
The vcontents of this article are: - Etiology of TFCC and ECU injuries in tennis, - Acute trauma injuries (in tennis), - Chronic overload injuries, - Positive ulnar variance, - Management and treatment for TFCC and ECU injuries, - Unload, block & redirection tape for TFCC and ECU injuries and - Tennis specific unload, block and redirection tape technique.